62.9k views
4 votes
Help, i know the answer but i don’t know how to do the work

Help, i know the answer but i don’t know how to do the work-example-1
User Yorodm
by
4.9k points

1 Answer

5 votes

Answer:

C

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Simplifying each radical before combining them.


√(45t)

=
√(9(5t))

=
√(9) ×
√(5t) = 3
√(5t)

-----------------------------------------------------------------------------


√(125t)

=
√(25(5t))

=
√(25) ×
√(5t) = 5
√(5t)

---------------------------------------------------------------------------

Hence

2(3
√(5t)) - 3(5
√(5t)

= 6
√(5t) - 15
√(5t)

= - 9
√(5t) → C

User Pallie
by
4.7k points